IMPLEMENTASI MODEL PEMBELAJARAN PJBL (PROJECT BASED LEARNING) PADA MATERI SURAT RESMI DI SMPN 12 PEKANBARU - Khairunnisa; Elvrin Septyanti; Oki Rasdana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The type of research used by the author in this study is quantitative research. The type of quantitative research used by the author is using experimental design. This experimental design consists of two groups, namely the control group and the experimental group. Before learning, both classes were pretested for differences in initial conditions between the control group and the experimental group. This research was carried out at SMPN 12 Pekanbaru. The location of this school is on Jalan Guru Sulaiman No.37, Padang Bulan, Senapelan District, Pekanbaru City, Riau Province. This research plan is to process and report on research results from December 2024 to May 2025. Based on the results of the analysis and research that has been carried out by researchers, it can be concluded that the application of the Project Based Learning (PjBL) learning model has a significant impact on improving the writing skills of official letter writing skills of grade VII students of SMPN 12 Pekanbaru. The conclusion obtained, that before the treatment was given, the pretest results showed that the initial ability of students in writing official letters was still relatively low and moderate. After the implementation of project-based learning, there was a marked increase, especially in the experimental class, which showed an average score increase from 72.5 to 83.5 with the ability category changing from medium to high. These findings are reinforced by the results of the Wilcoxon test and regression test which show a significant difference between pretest and posttest scores, as well as a strong linear relationship between the application of the learning model and student learning outcomes.